Pathogenicity and transmissibility of North American triple reassortant swine influenza A viruses in ferrets. - Subrata Barman; Petr S Krylov; Thomas P Fabrizio; John Franks; Jasmine C Turner; Patrick Seiler; David Wang; Jerold E Rehg; Gene A Erickson; Marie Gramer; Robert G Webster; Richard J Webby (PLoS Pathogens)
North American triple reassortant swine (TRS) influenza A viruses have caused sporadic human infections since 2005, but human-to-human transmission has not been documented. These viruses have six gene segments (PB2, PB1, PA, HA, NP, and NS) closely related to those of the 2009 H1N1 pandemic viruses. Therefore, understanding of these viruses' pathogenicity and transmissibility may help to identify determinants of virulence of the 2009 H1N1 pandemic viruses and to elucidate potential human health threats posed by the TRS viruses. Here we evaluated in a ferret model the pathogenicity and transmissibility of three groups of North American TRS viruses containing swine-like and/or human-like HA and NA gene segments. The study was designed only to detect informative and significant patterns in the transmissibility and pathogenicity of these three groups of viruses. We observed that irrespective of their HA and NA lineages, the TRS viruses were moderately pathogenic in ferrets and grew efficiently in both the upper and lower respiratory tracts. All North American TRS viruses studied were transmitted between ferrets via direct contact. However, their transmissibility by respiratory droplets was related to their HA and NA lineages: TRS viruses with human-like HA and NA were transmitted most efficiently, those with swine-like HA and NA were transmitted minimally or not transmitted, and those with swine-like HA and human-like NA (N2) showed intermediate transmissibility. We conclude that the lineages of HA and NA may play a crucial role in the respiratory droplet transmissibility of these viruses. These findings have important implications for pandemic planning and warrant confirmation.